Penerapan Metode Interpretive Structural Modeling (ISM) Dalam Menyusun Perancangan Pengolahan Limbah Ampas Kopi Aroma Kahuripan - Manasye Surya Sanjaya (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
Coffee grounds waste, which is rich in carbon, can accelerate global warming if not managed properly, considering its contribution to the greenhouse effect (Hendra Arthaviana, 2019). Therefore, coffee grounds can have a negative impact on the environment if they are not processed or utilized. So, coffee grounds need to be processed into useful products so as not to pollute the environment. The method used in this research is interviews. Based on the results of the application of the ISM (Interpretative Structural Modeling) method which was carried out regarding the coffee grounds waste processing strategy, it was concluded that the application of the ISM method can be used to review the main constraint elements and objectives of processing coffee grounds waste at Aroma Kahuripan